Polarization Effects of GaN and AlGaN: Polarization Bound Charge, Band Bending, and Electronic Surface States - Eller, Brianna S.; Yang, Jialing; Nemanich, Robert J. (Journal of electronic materials, 2014)
GaN-based devices are currently limited by reliability issues such as gate leakage and current collapse, where the mechanisms responsible for degradation are closely related to the electronic surface state configuration. Therefore, understanding the electronic surface state configuration of GaN-based materials will help improve device performance. Since GaN has an inherent polarization, these materials are also subject to a bound polarization charge, which influences the electronic state configuration. In this study, the surface band bending of N-face GaN, Ga-face GaN, and Ga-face AlGaN was measured with x-ray photoemission spectroscopy after various cleaning steps to investigate the effects of the polarization. Despite the different surface bound charge on these materials, similar band bending was observed regardless of the magnitude or direction of the charge. Specifically, the band bending varied from −0.1 eV to 0.9 eV on these samples, which supported the models of a Fermi level pinning state at ∼0.4 eV to 0.8 eV below the conduction band. Based on available literature, we suggest this pinning state is indirectly evident of a nitrogen vacancy or gallium-dangling bond.